Influense of Indole Butyric Acid (IBA) for Stenting Propagation of Cut Rose - Tizazu, Tadele Yeshiwas; Workie, Melkamu Alemayehu; Damot, Getachew Alemayehu (Current Research in Agricultural Sciences, 2018)
Growth promoting hormones like auxins are now a day commercially used for rooting of many ornamental plants including roses in propagation industries of many countries. Their effects are however influenced by environmental conditions, types of plants, the rooting media and the concentrations used. This research was therefore mainly conducted to evaluate the effects of different IBA concentrations on growth and development of stenting-propagated roses. The experiment was laid down in completely randomized design with four replications in the propagation house of Tana Flora PLC. The performance of rose cuttings treated with 1500 ppm of IBA was the best in all growth parameters including shoot length, Root length, toot number etc. which can be recommended to propagate roses by stenting method in the study area.